VIRGINIA WOOLF'S AESTHETIC VIEWS AND THE CONCEPTION OF MODERNIST PROSE - Xojimirzayeva Gulmira Baxriddin qizi (International Journal of Literature and Language Studies, 2026)
Annotation: This article provides a broad analysis of Virginia Woolf's aesthetic views and the formation of her conception of modernist prose. Her manifesto-articles